2000
DOI: 10.1034/j.1600-0501.2000.011001026.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate functional loading of Brånemark single tooth implants

Abstract: A clinical and radiographical study was performed to evaluate the treatment outcome of single tooth replacements with artificial crowns retained to implants installed according to a 1-stage surgical procedure and immediate loading (Experimental Group = EG) in comparison to the original 2-stage concept (Control Group = CG). The EG comprised 14 patients (= 14 implants) and the CG comprised 8 patients (= 8 implants), all with single tooth losses anterior to the molars. Beyond the non-smoking criterion the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
170
3
14

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(193 citation statements)
references
References 12 publications
6
170
3
14
Order By: Relevance
“…MBL values reported in this study were lower compared to other studies with similar observation periods (Boronat et al, 2008;Collaert and De Bruyn, 2008;Testori et al, 2008;Tözüm et al, 2008;Bergkvist et al, 2009;Piao et al, 2009;Song et al, 2009). Bone loss for healed sites (group I) in our study was about 0.266 ± 0.176 mm while with another study it showed an increase of up to 0.78 mm (Ericsson et al, 2000), which can be explained by the formation of the biological width (Hermann et al, 2001). In another reports, with the same implant systems, the mean value of MBL was 0.40 ± 1.43 mm (Cooper et al, 2010) and 0.40 ± 1.51 mm (De Bruyn et al, 2013) for a 3 years observation period.…”
Section: Discussionmentioning
confidence: 64%
“…MBL values reported in this study were lower compared to other studies with similar observation periods (Boronat et al, 2008;Collaert and De Bruyn, 2008;Testori et al, 2008;Tözüm et al, 2008;Bergkvist et al, 2009;Piao et al, 2009;Song et al, 2009). Bone loss for healed sites (group I) in our study was about 0.266 ± 0.176 mm while with another study it showed an increase of up to 0.78 mm (Ericsson et al, 2000), which can be explained by the formation of the biological width (Hermann et al, 2001). In another reports, with the same implant systems, the mean value of MBL was 0.40 ± 1.43 mm (Cooper et al, 2010) and 0.40 ± 1.51 mm (De Bruyn et al, 2013) for a 3 years observation period.…”
Section: Discussionmentioning
confidence: 64%
“…In this context, a critical evaluation of publications in the field of single-tooth replacement is required. Thus, despite the use of an immediate or earlycemented crown restoration on an implant, functional loading was applied after an additional period of healing in several studies (Ericsson et al 2000, Chaushu et al 2001, Andersen et al 2002, Malo et al 2003, Norton 2004, Ottoni et al 2005). There are a few studies on immediate functional loading of implants used for single-tooth replacement (Calandriello et al 2003a, 2003b, Cannizzaro & Leone 2003, Glauser et al 2003, Lindeboom et al 2006).…”
Section: Load Timing and Marginal Bone Level Changesmentioning
confidence: 99%
“…Due to a desire to increase the overall efficiency of the process, as well as an idea that outcomes may be improved, the concept of immediate placement and loading of implants began to emerge. [3] By placing an implant immediately after extraction, the overall treatment time would be shortened, theoretically increasing patient satisfaction and possible acceptance of treatment, as well as reducing overall costs incurred by the treating dentist. Soon, investigators began to discover that placement of a temporary restoration (immediate loading) might improve the overall esthetic outcome of implants placed in such a manner, as well as further shorten treatment time, by eliminating the need for an additional procedure to expose the implant (second stage surgery).…”
Section: Introductionmentioning
confidence: 99%
“…Soon, investigators began to discover that placement of a temporary restoration (immediate loading) might improve the overall esthetic outcome of implants placed in such a manner, as well as further shorten treatment time, by eliminating the need for an additional procedure to expose the implant (second stage surgery). [1,2,3] Immediate implant loading can be briefly defined as the loading of a dental implant immediately or few hours after being placed. Misch and coworkers defined as immediate occlusal loading within two weeks of implant insertion.…”
Section: Introductionmentioning
confidence: 99%